Protective Bitumen-Resin Coatings Based on Aromatic Petroleum Resin; AIP Conference Proceedings; Vol. 2051 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2018 (AMHS’18) - Bondaletov V. G. Vladimir Grigoryevich; Vosmerikov A. V. Aleksandr; Bondaletova L. I. Lyudmila Ivanovna; Nguyen Van Thanh; Bondaletova A. V. Anna (2018, 2018)
Title screen